Video game playing among preschoolers: prevalence and home environment in three provinces from Turkey. - Yalçın, S. Songül; Çaylan, Nilgün; Erat Nergiz, Meryem; Oflu, Ayşe; Yıldız, Deniz; Tezol, Özlem; Çiçek, Şeyma; Yurdakök, Kadriye (International Journal of Environmental Health Research, 2022)
We aimed to investigate the video game habits and their relationship with home environment in children 2–5 years in Turkey. A structured questionnaire about the child's demographic, screen, and video gaming characteristics was completed by parents in five health centers from three provinces. One-quarter of 1245 preschoolers were found to play video games. The prevalence of playing video games was higher in older age, male gender, low parental education, families with 3 or more children, having a game console, computers and tablets at home, child's screen time of more than 2 hours per day, child's non-compliance with the parental screen rules, and presence of someone else playing videogame at home. Of the parents, 54.5% did not know the name of the video game the child was playing. Parents should be counseled about supervising on their children's video game playing habits and selection of well-designed games with the right content.